The Soldiers of “Civilization” at the origins of Julio Roca’s Military Model. Argentina, 1878-1880 - Codesido, Lucas (Revista Complutense de Historia de América, 2022)
This article analyzes the actions carried out toward the renovation of military hierarchies and the political discourse associated with them, at the time that Julio Roca entered the political scene as head of the Ministry of War and Navy. In a short span of time at the turn of the decade between the 70’s and the 80’s of the 19th century, a series of events took place that modified the physical, political and institutional map or the Argentine Republic, crystallizing some of the forms of the state and styles of republics that were in dispute during those years. We are interested in examining the military policy bolstered by the national government, as of the moment when Julio Roca took charge of the Ministry of War at the beginning of 1878, from a perspective that will allow us to distinguish the role of the military forces (National Guard-Frontier Army) in the state’s process of advancement toward the south of the territory and help us to understand the role assigned, in that enterprise, to the subaltern members of the armed forces.